If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13v + -4v + 2v = -22 Combine like terms: 13v + -4v = 9v 9v + 2v = -22 Combine like terms: 9v + 2v = 11v 11v = -22 Solving 11v = -22 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Divide each side by '11'. v = -2 Simplifying v = -2
| ((x^2-2x-24)/(4x^3-5x^2))*((x^3-x^2)/(2x-12)) | | -4x+2=-2(3y+3) | | -2(m-3)=-6m+8 | | -7=-5-K | | x-1/2-7=x-1/3 | | D(x)=-6/x^2-9 | | 100+-53= | | 25/187.50 | | -2m-6=-6m+8 | | 6(x-2)-x=4(x+4)+7 | | -5y=-20+-25 | | 15=10p-5-3p | | -6/x^2-9 | | -2.6(x-8)+4.2=11 | | 187.5/25 | | x^2=x^2-3x | | -5y=-20+-20 | | 3a+3-11a=3a+36 | | logb81=2/3 | | u-7+2(2u+1)=-7(u+2) | | -16t^2+10t+50=0 | | 2x-10=-59+9z | | s-(5-3x)=7x+4 | | 5y+1+y=3y+19 | | -1(2-2n)=0 | | 5y+1+y=3y | | 2(6x+7)+9=12x+23 | | (2x+9)+6=2 | | 2.2-5.4v=17.86 | | 5z-3=-19+9z | | 2y=5x-10forx | | 6t+3(5t-4)=12(2t)-5 |